PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN DAN VARIAN RETURN TERHADAP BID - ASK SPREAD PADA MASA SEBELUM DAN SESUDAH STOCK SPLIT DI BURSA EFEK JAKARTA PERIODE 2000 - 2004 - Syaichu, Muhamad; Puspito, Novia Ike (JURNAL BISNIS STRATEGI, 2007)
Emitter as a company can not run from various economic occurrences. These economic occurrences are accepted by market as information that will be responded by all market participle troughs the stocks trade activity in capital market. Stock split is an activity to increase the number of stocks and will influence the stocks liquidity. One of the responses can be perceived by bid-ask spread.This research aims to analyze whether stock price, trading volume and variance of return have an effect to bid-ask spread around the announcement of stock split. In addition, this research also aims to examine the influence of the announcement of stock split on bid-ask spread. This research used 39 companies announcing of stock split in the Jakarta Stock Exchange during 2000-2004. Perception was conducted 5 days before until 5 days after stock split. A multiple regression analysis was used to examine the effect of stock price, trading volume and variance of return on bid-ask spread. Furthermore, this research used paired sample t-test analysis to examine the different of bid-ask spread before and after the announcement of stock split.The result indicates that stock price had a positive insignificant influence on bid-ask spread before stock split, but stock price had a positive significant influence on bid-ask spread after stock split. Trading volume and variance of return had a positive significant influence on bid-ask spread before and after stock split. The result also shows that there was significant difference between bid-ask spread before and after the announcement of stock split.